Koszty działalności ubezpieczeniowej w zarządzaniu kosztami zakładu ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Costs of insurance activity in cost management in insurance company, 2009)
Cost management is the most important part of management process in such an institution as an insurance company because of financial product and the need for financial liquidity management. Polish insurance companies have been looking after their costs for few years what is presented in insurance market analysis. Cost management process contains such tasks as: finding out common elements for the chosen strategy of insurance company and costs reduction, preparing the partition strategic tasks on three insurance company activity areas, selection and elaboration of proper cost accounting system, preparation costs budgeting, monitoring actions and operations, preparing costs calculation report according to received early costs classification, control and deviations analysis and the estimation of cost management process application. For management cost of insurance activity could be classified for acquisition costs, adjustment costs, recourses and recoveries costs and administrative costs. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, Nr 53, s. 20-28